Yield performance of loquat trees grafted on quince cultivar Portugal - Pio, Rafael; Orto, Fernando Antônio Campo Dall; Barbosa, Wilson; Chagas, Edvan Alves; Ojima, Mário; Feldberg, Nelson Pires (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to compare the performance of five loquat selections grafted on quince seedlings and on loquat seedlings. The following selections were assessed: IAC 966-23, IAC 265-66, IAC 1467-25, Mizauto (IAC 167-4) and Mizumo (IAC 1567-411). The selections were grafted in rooted cuttings of quince cultivar Portugal (planted at the field with an spacing of 4x2 m, corresponding to a density of 1,250 plants ha-1) and in loquat seedlings (planted at the field with an spacing of 7x4 m, corresponding to a density of 357 plants ha-1). The experiments were carried in Monte Alegre do Sul, SP, Brazil. Production (kg and number of the fruits per plant), fruit average mass (g) and productivity (Mg ha-1), along three years of plantation at the field, were evaluated. After the last harvest, the average of all harvests was calculated. The IAC 265-66 selection showed the best performance when grafted on quince and loquat rootstocks. Despite the lower production, there was no difference in productive between quince and loquat as rootstocks. The use of quince as rootstock is an option for loquat cultivation, mainly due to the plant size reduction and consequently, the easier cultural practices.
Keywords: Cydonia oblonga; Eriobotrya japonica; fruit quality